EPCT-15. THE REMIND TRIAL: MULTI-ANTIGEN TARGETED T CELLS FOR PEDIATRIC CNS TUMORS. (4th December 2020) - Grant, Melanie; Fortiz, Maria Fernanda; Wang, Lu; Lang, Haili; Datar, Anushree; Reynolds, Emily; Terpilowski, Madeline; Lazarski, Chris; Tanna, Jay; Pitino, Adriana; Zhang, Nan; Hoq, Fahmida; et al.
Abstract: BACKGROUND: Patients with relapsed CNS malignancies or DIPG face terrible prognoses. We hypothesized that T cells specific for 3 tumor-associated antigens (TAA), WT1, PRAME and survivin, would be safe and elicit anti-tumor immunity. METHODS: Patients (n=9) have received autologous tumor antigen-associated T cells (TAAT) (up to 4x10 7 /m 2 ) for newly diagnosed DIPG (Group A) or recurrent CNS malignancies (Group B) on a Phase I dose-escalation study (NCT03652545) and were monitored for safety and response. RESULTS/ DISCUSSION: 9/9 patients who received TAAT completed the 45-day safety monitoring phase with no dose-limiting toxicities. Infused cells were predominantly CD3+ T cells (median 96%; range: 87–99%), with CD4+ and CD8+ comprising 16% (range: 5–87%) and 40% (range: 4–67%) of the CD3+ cells, respectively. TAAT with specificity for 1–3 TAAs, at varying frequencies, was demonstrated in 8/9 TAAT by anti-IFN-γ ELISPOT. Plasma cytokine profiles demonstrated infusion-related immune cytokine responses. In summary, TAAT are safe and may elicit anti-tumor responses in vivo. To confirm TAAT-driven effects, we are evaluating plasma proteomic profiles for immune-response signatures and assessing unique T cell receptor rearrangements of infused TAAT. Response assessment and dose escalation are ongoing.